Reasons for the immigration of Hainanese Muslim overseas Chinese to Malaya (1870-1939): from a push-pull perspective - Ye, Halimah Zhiping; Azlizan Mat Enh; Suffian Mansor (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examines the multiple driving factors behind the migration of Chinese Muslims from Hainan Island to Malaya from the late Qing Dynasty to the mid-20th century. Based on the push-pull theory of migration, the study employs qualitative methods and draws on a wealth of primary sources—including official archives, local annals, genealogies, and oral histories—to analyse how political, economic, and religious forces shaped this migration process. The study found that institutional oppression of Muslims, social unrest, and multiple forms of marginalisation constituted persistent push factors, while Malaya's economic prospects, religious tolerance, and established Muslim networks played significant pull roles. Through case studies of individuals such as Ha Shuzhang（Haji Hassan Salleh), the study demonstrates that this migration was both a response to structural violence and an active pursuit of religious preservation and community reconstruction. It reveals the complex dynamics of transnational mobility among Chinese Muslims and highlights the central role of Islam in shaping the diaspora experience. By shedding light on a long-neglected subgroup within the Chinese Muslim community, this study fills a critical gap and provides detailed insights into overseas Chinese studies, offering a broader perspective on understanding ethnic and religious pluralism in colonial-era Southeast Asia.